Study on the accuracy of CA-125 combined with Transvaginal Ultrasound for presurgical Diagnosis of Endometriosis - Thapa, Kritika; Rawal, Suniti; Jha, Anamika (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Endometriosis is a gynecological condition often diagnosed surgically. Non-invasive tools such as CA125 and transvaginal sonography (TVS) may improve early detection. Methods: This descriptive observational study was conducted from April 2017 to October 2018. A total of 77 women with a clinical diagnosis of endometriosis underwent evaluation using serum CA125 and TVS. Surgical and histopathological findings were used as the gold standard. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: A total of 85 patients were initially included; however, eight were excluded because they did not meet the inclusion criteria. The mean age of the participants was 35.5 years. Dysmenorrhea was the most common symptom, followed by deepseated lower abdominal pain. When the cutoff of CA125 was taken as 35 IU/ml, sensitivity, specificity, PPV, and NPV were 98.6%,0%,90.8%, and 0% respectively, with an accuracy of 89.6%. ROC curve determined the cut-off point of 55 IU/ml for CA125 with a PPV of 95.7%. Endometriosis was present in 90.9% cases during surgery and was proven histopathologically in 80.5%. A combination of CA125 and endometrioma in TVS had a sensitivity of 80% with an accuracy of 80%. Conclusion: The combined use of CA125 and TVS improves preoperative diagnostic accuracy for endometriosis and may reduce reliance on invasive procedures. Thus, these can be used for initial assessment to avoid diagnostic delay and enable the clinician to plan appropriate surgical treatment.